Nilotinib: optimal therapy for patients with chronic myeloid leukemia and resistance or intolerance to imatinib - Ronan Swords; Devalingam Mahalingam; Swaminathan Padmanabhan; Jennifer Carew; Francis Giles (Dove Medical Press, 2009)
Ronan Swords, Devalingam Mahalingam, Swaminathan Padmanabhan, Jennifer Carew, Francis GilesInstitute for Drug Development, Cancer Therapy and Research Centre, University of Texas Health Science Centre at San Antonio, USAAbstract: Chronic myeloid leukemia (CML) is the consequence of a single balanced translocation that produces the BCR-ABL fusion oncogene which is detectable in over 90% of patients at presentation. The BCR-ABL inhibitor imatinib mesylate (IM) has improved survival in all phases of CML and is the standard of care for newly diagnosed patients in chronic phase. Despite the very significant therapeutic benefits of IM, a small minority of patients with early stage disease do not benefit optimally while IM therapy in patients with advanced disease is of modest benefit in many. Diverse mechanisms may be responsible for IM failures, with point mutations within the Bcr-Abl kinase domain being amongst the most common resistance mechanisms described in patients with advanced CML. The development of novel agents designed to overcome IM resistance, while still primarily targeted on BCR-ABL, led to the creation of the high affinity aminopyrimidine inhibitor, nilotinib. Nilotinib is much more potent as a BCR-ABL inhibitor than IM and inhibits both wild type and IM-resistant BCR-ABL with significant clinical activity across the entire spectrum of BCR-ABL mutants with the exception of T315I. The selection of a second generation tyrosine kinase inhibitor to rescue patients with imatinib failure will be based on several factors including age, co-morbid medical problems and ABL kinase mutational profile. It should be noted that while the use of targeted BCR-ABL kinase inhibitors in CML represents a paradigm shift in CML management these agents are not likely to have activity against the quiescent CML stem cell pool. The purpose of this review is to summarize the pre-clinical and clinical data on nilotinib in patients with CML who have failed prior therapy with IM or dasatinib.Keywords: nilotinib, chronic myeloid leukemia, imatinib